Participation in organized leisure-time activities and risk behaviors in Czech adolescents - Badura, Petr; Sigmundova, Dagmar; Sigmund, Erik; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of public health, 2017)
OBJECTIVES: The study aimed to assess the associations between participation in organized leisure-time activities (OLTA) and risk behaviors, and whether the associations differed by gender, age, and pattern of OLTA involvement. METHODS: Data from the 2013/2014 Health Behaviour in School-Aged Children study on 10,279 11-, 13-, and 15-year-old Czech adolescents (49.2% boys) were used. We assessed the associations between OLTA participation and risk behaviors, and modification by age and gender. RESULTS: OLTA participants were less likely to smoke, get drunk repeatedly, or skip school and, in contrast, more likely to get injured and fight repeatedly. The associations with lower occurrence of risk behaviors were the strongest for artists, while none was significant for adolescents participating only in team sports. Girls participating in OLTA had lower odds to smoke, get drunk, or skip school than boys, and these boys had higher odds to get injured or fight. CONCLUSIONS: OLTA participation is associated with lower occurrence of repeated substance use and truancy and inversely with higher odds for physical fights and injuries. Girls, in general, are at lower risk when participating in OLTA than boys.
Keywords: Violence; Extracurricular activities; Sex Distribution; Truancy; Female; Risk-Taking; dítě; rozložení podle pohlaví; sporty; ženské pohlaví; Adolescent; volnočasové aktivity; lidé; absentérství; Bullying; Wounds and Injuries; Substance use; školy; Schools; násilí; Leisure Activities; Absenteeism; Male; Czech Republic; Sports; Česká republika; Substance-Related Disorders; Child; rány a poranění; mužské pohlaví; poruchy spojené s užíváním psychoaktivních látek; Adolescents; riskování; mladiství; Humans